Long Wavelength （1.2-1.5μm）Semiconductor Lasers - Pan Zhonghou; Yang Guisheng; Ran Congzhu; Zhao Songshan; Wang Yuzhang (Tongxin xuebao, 1984)
Long wavelength semiconductor lasers are the important sources for the high capacity, long repeater spacing fiber-optic telecommunications. This paper report the 1.2μm, 1.3μm, 1.5μm lasers, its power feedback and temperature feedback apparatus and single-mode coupling.